Muscular strength and endurance adaptations to functional resistance training in young elite field hockey players - Gürkan, Alper Cenk; Eraslan, Meriç; Aydın, Serhat; Altuğ, Tolga; Türkmen, Mustafa; Söyler, Mehmet; Mülhim, Mustafa Alper; Şahin, Musa; Karataş, Baykal; Akcan, İbrahim Orkun; Küçük, Hamza (Frontiers in Physiology, 2025)
BackgroundFunctional strength training (FST) has gained considerable attention due to its potential in enhancing muscle strength, endurance, and body composition, especially among athletes. The purpose of this study was to assess the effects of a 12-week FST program on performance outcomes such as muscle strength, muscular endurance, and body composition in elite male field hockey players.MethodsThe study involved 28 male athletes from the Türkiye Hockey Federation Super League, with a mean age of 27.54 ± 1.34 years and an average athletic experience of 7.62 ± 0.48 years. The mean height of participants was 180.28 ± 4.54 cm, and their mean weight was 75.59 ± 3.08 kg. Participants were randomly divided into two groups: the experimental group (n = 14) and the control group (n = 14). Pre-intervention assessments were conducted to evaluate muscle strength (Leg Extension, Leg Curl, Bench Press, Pushdown), muscular endurance (30-s Sit-up and Push-up tests), and body composition [Body Mass Index (BMI) and Body Fat Percentage (BFP)]. The experimental group participated in the FST program three times per week for 12 weeks, while the control group maintained their usual training regimen. Post-test evaluations were performed using the same testing protocols. Statistical Analysis: Data were analyzed using two-way repeated measures ANOVA to assess the interaction effects of group and time (pre-test vs post-test). Partial eta squared (η2) values were used to report effect sizes, and statistical significance was set at p < 0.05. Data analysis was carried out using SPSS 22.0 software. Normality was assessed through the Shapiro-Wilk test, and data distribution was further examined through skewness-kurtosis values, histograms, box plots, and Q-Q plots. Paired sample t-tests were performed for pairwise comparisons, with Cohen’s d used to determine the effect sizes. The classification for effect sizes followed Hopkins’ (2002) guidelines: small (≥0.01), moderate (≥0.06), and large (≥0.14).ResultsSignificant group × time interaction effects were found for all measured variables (p < 0.05). The experimental group showed greater improvements in body composition, muscle strength, and muscular endurance compared to the control group. Specifically, the experimental group experienced a significant reduction in BMI (pre-test: 21.17 ± 0.64 kg/m2, post-test: 19.84 ± 0.85 kg/m2, p < 0.001) and BFP (pre-test: 15.36% ± 0.62%, post-test: 12.13% ± 0.47%, p < 0.001), while the control group showed minimal changes in these variables. Muscle strength improvements in the experimental group were significant for Leg Extension (pre-test: 83.93 ± 4.87 kg, post-test: 66.07 ± 4.01 kg, p = 0.003), Leg Curl (pre-test: 99.29 ± 7.81 kg, post-test: 118.21 ± 5.04 kg, p < 0.001), and Bench Press (pre-test: 66.43 ± 6.91 kg, post-test: 87.14 ± 4.69 kg, p < 0.001). In contrast, the control group did not show significant improvements in these tests. Muscular endurance was also superior in the experimental group for both the 30-s Sit-up (pre-test: 19.21 ± 0.97, post-test: 23.36 ± 1.28, p < 0.001) and Push-up (pre-test: 24.66 ± 2.53, post-test: 27.04 ± 0.81, p < 0.001) tests. Effect sizes (Cohen’s d) indicated moderate to large effects for all measured variables, with d values ranging from 0.46 to 1.14 for strength and endurance improvements.ConclusionThe findings of this study demonstrate that a 12-week FST program significantly improves muscle strength, endurance, and body composition in elite male field hockey players. These results suggest that incorporating FST into athletic training regimens may optimize performance and enhance overall physical fitness in athletes.